Relative Impact of Right Ventricular Electromechanical Dyssynchrony Versus Pulmonary Regurgitation on Right Ventricular Dysfunction and Exercise Intolerance in Patients After Repair of Tetralogy of Fallot - Lumens, Joost (J Am Heart Assoc, 2019)
BACKGROUND: The relative impact of right ventricular (RV) electromechanical dyssynchrony versus pulmonary regurgitation (PR) on exercise capacity and RV function after tetralogy of Fallot repair is unknown. We aimed to delineate the relative effects of these factors on RV function and exercise capacity. METHODS AND RESULTS: We retrospectively analyzed 81 children with tetralogy of Fallot repair using multivariable regression. Predictor parameters were electrocardiographic QRS duration reflecting electromechanical dyssynchrony and PR severity by cardiac magnetic resonance. The outcome parameters were exercise capacity (percentage predicted peak oxygen consumption) and cardiac magnetic resonance ejection fraction (RV ejection fraction). To understand the relative effects of RV dyssynchrony versus PR on exercise capacity and RV function, virtual patient simulations were performed using a closed‐loop cardiovascular system model (CircAdapt), covering a wide spectrum of disease severity. Eighty‐one patients with tetralogy of Fallot repair (median [interquartile range IQR] age, 14.48 [11.55–15.91] years) were analyzed. All had prolonged QRS duration (median [IQR], 144 [123–152] ms), at least moderate PR (median [IQR], 40% [29%–48%]), reduced exercise capacity (median [IQR], 79% [68%–92%] predicted peak oxygen consumption), and reduced RV ejection fraction (median [IQR], 48% [44%–52%]). Longer QRS duration, more than PR, was associated with lower oxygen consumption and lower RV ejection fraction. In a multivariable regression analysis, oxygen consumption decreased with both increasing QRS duration and PR severity. CircAdapt modeling showed that RV dyssynchrony exerts a stronger limiting effect on exercise capacity and on RV ejection fraction than does PR, regardless of contractile function. CONCLUSIONS: In both patient data and computer simulations, RV dyssynchrony, more than PR, appears to be associated with reduced exercise capacity and RV systolic dysfunction in patients after TOF repair.